HARDINESS, EFIKASI DIRI DAN PROBLEM FOCUSED COPING PADA ANAK BUAH KAPAL BERSTATUS LAJANG DI KRI “X” TNI ANGKATAN LAUT - Dian Damayanti; Dewi Mustami’ah; Fauziah Julike Patrika (Fakultas Psikologi Universitas Hang Tuah, 2021)
This study aims to determine the relationship between hardiness and self-efficacy with problem focused coping on crew members of KRI 'X' Indonesian Navy with Single status in Surabaya. Respondent ABK KRI 'X' Indonesian Navy in Surabaya who has a single status. A total of 60 respondents were selected using a saturated sampling technique. The scale used in this study is the hardiness scale, self-efficacy scale, and problem focused coping scale. The analysis technique used is product moment correlation and multiple correlation. The results showed that there was a simultaneous relationship between hardiness and self-efficacy with problem focused coping. The findings also show that hardiness and self-efficacy show a positive direction towards problem focused coping. The results of this study can be used as a reference related to the problem of problem focused coping on crew members of the KRI Navy who are single.